Azurocidin in gingival crevicular fluid as a potential biomarker of chronic periodontitis. (14th October 2019) - Nalmpantis, Dimitrios; Gatou, Asimina; Fragkioudakis, Ioannis; Margariti, Apostolia; Skoura, Lemonia; Sakellari, Dimitra
Abstract: Background and Objective: Azurocidin is a neutrophil‐derived protein in gingival crevicular fluid (GCF) which, according to relevant studies, might correlate with periodontal disease. The aim of the present study was to evaluate azurocidin as a potential biomarker for chronic periodontitis. Material and Methods: One hundred and one patients participated in the study, divided into two groups. Forty‐eight were included in the periodontally healthy group (HP) and fifty‐three in the chronic periodontitis group (CP). Clinical indices included probing depth (PD), recession (REC), clinical attachment level (CAL), bleeding on probing (BOP) and plaque (PL). Pooled GCF samples were collected with paper strips, freezed in liquid nitrogen (−196°C), stored at −80°C, and the levels of azurocidin were analyzed with ELISA. Values were transformed and expressed for comparisons in pg/30 s sample. Statistical comparisons were performed using non‐parametric tests (Mann‐Whitney) at the 0.05 level. Furthermore, the diagnostic accuracy of the procedure was assessed with receiver operator characteristic curves (ROC), areas under the curve (AUC), and the Youden's J Index calculated. Results: Demographic data were comparable between the two groups. Clinical parameters and the levels of azurocidin were statistically significantly higher in the CP group when compared to the HP group (Mann‐Whitney test, P  < .05). Quantitative data from ELISA demonstrated a high diagnostic accuracy of azurocidin, with AUC calculated higher than 0.9 at the 0.000 level. Conclusion: Azurocidin in GCF is a promising biomarker for periodontal disease. The results of the present study agree with previous studies in the literature showing an up‐regulated trend in the levels of azurocidin in periodontitis patients.